A Fashion Hub Utilizing Hybrid Architectural Design in West Jakarta:Langgam Wastra Nusantara - Ribka Agatha; Ari Rahadini; Saratri Wilonoyudho (Canopy: Journal of Architecture, 2025)
T&P (Textile and Products) industry forms a foundational pillar of Indonesia's creative economy, as delineated in the UNESCO Framework for Cultural and Creative Industries (2009). It substantially drives employment creation (accounting for over 3.8 million jobs in 2022; Badan Pusat Statistik, 2023) and  reinforces  the  national  manufacturing  sector  amid  global  value  chain  integration. Leveraging  its  profound  cultural  patrimony  and  multifaceted  textile  legacy,  Indonesia  has established itself as a preeminent global fashion center and among the foremost fashion exporters in 2022, with forecasts anticipating sustained expansion of the domestic fashion industry's valuation through 2029.  However, the industry also faces challenges of order attrition, deindustrialization, restricted entry, fragmentation of industry players, and the flooding of the domestic market with imported products.  The optimization of indigenous cultural assets, notably wastra Nusantara, is positioned as a strategic approach to improving both inclusivity and competitiveness within the national fashion ecosystem. Langgam Wastra Nusantara embodies a novel architectural approach that  integrates  collaborative,  promotional,  and  commercial  functions  to  strengthen  the nationalindigenous  textile  industry.  The  design  synthesizes  traditional  fabrics  with  wastra  Nusantara, establishing a platform that is both adaptable and capable of competing within the global fashion. This initiative is further reinforced by its strategic location in the Administrative City of West Jakarta, which provides high accessibility, efficient distribution systems, and adequate supporting infrastructure for commercial purpose.